Recent Developments and Knowledge in Intelligent and Safe Marine Navigation (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
The maritime shipping sector toward intelligent and safe navigation is intrinsically tied to the integration of cutting-edge technologies (i.e., AI and big data). These technologies are being harnessed across multiple facets of the maritime domain. It is evident that these methodologies have the potential to significantly enhance the intelligence and safety of ships. This SI stands as a compendium of research papers that not only enrich the academic dialogue but also support substantial practical implications for the maritime industry. The insights and innovations contained within this SI are imperative in furthering the frontiers of intelligent and safe navigation. The contributions encompass a spectrum of recent developments, encompassing topics such as big data fusion for ship detection, collision avoidance through deep reinforcement learning approaches, and ship system identification, route planning, etc. These methods draw from a confluence of expertise, merging insights from ship science, AI, and their interdisciplinary interactions. Collectively, the research presented in this SI constitutes a vital stride in the ongoing endeavor to fortify and refine intelligent navigation.